2012
DOI: 10.1007/s11524-011-9655-5
|View full text |Cite
|
Sign up to set email alerts
|

Urban Inequities; Urban Rights: A Conceptual Analysis and Review of Impacts on Children, and Policies to Address Them

Abstract: This paper explores current conceptual understanding of urban social, environmental, and health inequality and inequity, and looks at the impact of these processes on urban children and young people in the 21st century. This conceptual analysis was commissioned for a discussion paper for UNICEF's flagship publication: State of the World's Children 2012: Children in an Urban World. The aim of the paper is to examine evidence on the meaning of urban inequality and inequity for urban children and young people. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 99 publications
(78 reference statements)
0
14
0
Order By: Relevance
“…The incidence of LBW in developing countries ranges from 5 to 33% with an average of 16.5% which is more than double the rate of 7% noted in developed regions [5]. For instance, the average incidence rate of LBW in Nigeria is 12% [6], but the actual incidence of LBW in developing countries may be difficult to determine because many deliveries occur in rural areas where health care is inaccessible and the newborns are not routinely weighed [7].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of LBW in developing countries ranges from 5 to 33% with an average of 16.5% which is more than double the rate of 7% noted in developed regions [5]. For instance, the average incidence rate of LBW in Nigeria is 12% [6], but the actual incidence of LBW in developing countries may be difficult to determine because many deliveries occur in rural areas where health care is inaccessible and the newborns are not routinely weighed [7].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of health, the most vulnerable young children may have been born at low birthweight to homeless mothers, and are at risk of malnutrition and infectious disease. However, in addition, urban populations are increasingly at risk of obesity and non-communicable diseases, changing the nature of the public health problems in LMICs (29).…”
Section: Rural and Urban Populationsmentioning
confidence: 99%
“…Older children are at risk of sexual abuse and, in many contexts, sexual slavery. Street children and adolescents are also at risk from alcohol and drug misuse (29), in addition to risks associated with living in an unsafe and unhealthy environment. Ultimately therefore the policy solutions to improve children's outcomes will differ according to where they live and the challenges they face.…”
Section: Rural and Urban Populationsmentioning
confidence: 99%
“…WHO through its Social Determinants for Health (SDH) review concluded, the situations under which people are born, live, work and age can cause unfair health disparities (9)(10)(11). Generally, health inequalities, including inequalities in child health are considered as inequity (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%